Efektifitas Fungsi Badan Kepegawaian Daerah Kabupaten Gorontalo dalam Penyelenggaraan Penerimaan Calon Pegawai Negeri Sipil - Ismail, Nurwita (Universitas Gorontalo)
In essence the right of everyone to get the same job and opportunity in government, is one of the instruments in trying to improve prosperity and prosperity of the people. This corresponds to the basic philosophy of the state summarized in Pancasila, where the five precepts of Pancasila should be viewed as one unified whole. Even has been translated in the Constitution of the Republic of Indonesia (UUD) Year 1945, as well as a constitutional basis in governance, nation and state.The importance of Gorontalo Regency Government / related agencies especially Regional Personnel Agency (BKD) performs acceptance in accordance with the mechanisms stipulated in several Laws and Regulations in particular PP. 43 of 2007, with the expectation that the quantity of civil servants can dominate the quality so that the public expectation of the quality of service and the acceleration of regional development can be fulfilled. Type of research Sociological Juridical. Juridical Sociological Research is a legal research that combines the research of normative law and sociological law research.